The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.24843/eja.2022.v32.i12.p11
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Performance, Kepemilikan Manajerial, Leverage, Profitabilitas dan Pengungkapan Corporate Social Responsibility

Abstract: The trend of CSR implementation changed when the pandemic started. The research aims to empirically re-examine the effect of environmental performance, managerial ownership, leverage and profitability on CSR disclosure in line with the agency, stakeholder and legitimacy theories. The object of research is the energy sector companies on the IDX with a population of 229 companies for the 2019-2021 period. The sample obtained is 131 observational data obtained by purposive sampling technique. The results of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…The results of this study are not in line with research conducted by Balamuralikrishnan & Gnanasekar (2020) which found that managerial ownership has a negative effect on dividend policy, which means that the greater the shares owned by managers, the smaller the dividends paid to shareholders. The results of this study are also in line with research conducted by Willi & Andewi (2017), Roos &Manalu (2019), andMerdekawati, Azizah, Santoso, &Hapsari, (2022) who found that managerial ownership has no effect on dividend policy. This is due to the fact that the shares owned by managerial ownership are not too large, besides that some of the companies sampled do not have shares owned by managers so this causes that the shares owned by managers have no effect on dividend policy.…”
Section: H₁: There Is An Effect Of Financial Leverage On Dividend Policysupporting
confidence: 91%
“…The results of this study are not in line with research conducted by Balamuralikrishnan & Gnanasekar (2020) which found that managerial ownership has a negative effect on dividend policy, which means that the greater the shares owned by managers, the smaller the dividends paid to shareholders. The results of this study are also in line with research conducted by Willi & Andewi (2017), Roos &Manalu (2019), andMerdekawati, Azizah, Santoso, &Hapsari, (2022) who found that managerial ownership has no effect on dividend policy. This is due to the fact that the shares owned by managerial ownership are not too large, besides that some of the companies sampled do not have shares owned by managers so this causes that the shares owned by managers have no effect on dividend policy.…”
Section: H₁: There Is An Effect Of Financial Leverage On Dividend Policysupporting
confidence: 91%